Content and acceptability of an Occupational Therapy Intervention in Homecare Re-ablement Services (OTHERS) - Whitehead, Phillip J.; Drummond, Avril E.R.; Parry, Ruth H.; Walker, Marion F. (SAGE, 2018)
Introduction: Despite clear compatibilities between the tenets of occupational therapy and re-ablement, there is limited research on occupational therapy in homecare reablement services. This paper describes the content of an occupational therapy intervention that was delivered in homecare re-ablement services as part of a feasibility randomised controlled trial (OTHERS). It also evaluates whether the intervention was acceptable to the participants who received it. Method: There were three phases. 1.) A bespoke pro forma was completed recording the activities undertaken after each therapy visit. 2.) An acceptability questionnaire was sent by post to every intervention participant. 3.) Semi-structured interviews were completed with key informants who received the intervention. Results/Findings: The principal activities undertaken were: assessment; case management; goal setting; advice and support; and practising activities. It was possible to implement a graded programme for participants’ main goals in relation to bathing/showering or kitchen activities. Participants particularly valued the advice and support provided, however, there were difficulties due to fluctuations in circumstances and with activities of daily living (ADL) outside the home. Participants also had outdoor mobility goals but there were difficulties working on these within the 6-week timescale. Conclusion: An intervention focussing on ADL within the home was acceptable for participants and consistent with their goals and objectives; however, they also had goals beyond personal ADL and the timescale of the re-ablement episode which were not met. Further research should focus on extended ADL at a later stage beyond the time-limited period.